Dinamika kawasan kesatuan pengelola hutan produksi Sorong Selatan - Raharjo, Syafrudin; Sinaga, Posma Pitta; Murdjoko, Agustinus (Cassowary, 2024)
Land cover changes continue to occur, bearing in mind that humans need resources and living space to continue to develop. Forest destruction is a form of change or dynamics of land termination, a problem in areas with extensive forest resources but high dependence on forests for people's lives. In Indonesia, KPH is the institution in charge of managing regional forests. With its forest area that is still maintained, Papua Island has many KPHs, one of which is the South Sorong KPHP. This study aims to determine the magnitude of changes in land cover, especially those that cause forest damage, such as deforestation and forest degradation, as well as other impacts caused by this damage, namely CO2 emissions. The research was conducted in the South Sorong KPHP working area from February to April 2023. This research used a descriptive method through map analysis. The results of the analysis of land cover for 2012 to 2021 show changes in land cover in forest areas causing forest damage in the form of deforestation and forest degradation. Deforestation in the last ten years reached 19,991.83ha, while the area of ​​forest degradation was 67,044.58ha. As a result of deforestation and forest degradation, forest carbon stocks are released and cause CO2 emissions. Deforestation CO2 emissions from the South Sorong KPHP area amounted to 13,418,062.28 tons of CO2, or around 70.68% of the total CO2 emissions, with an average emission of 1,341,806.23 tons of CO2/year. The highest CO2 emissions due to deforestation occurred in three periods, namely the periods 2016-2017, 2018-2019, and 2020-2021. Forest degradation contributes to CO2 emissions of 5,566,602.38 tons of CO2, or around 29.32% of the total CO2 emissions, with an average of 556,660.24 tons of CO2/year. Keywords: Land cover, forest destruction, deforestation, forest degradation, and CO2 emissions